2017
DOI: 10.1160/th16-06-0482
|View full text |Cite
|
Sign up to set email alerts
|

Identifying patients at high risk of heparin-induced thrombocytopenia-associated thrombosis with a platelet activation assay using flow cytometry

Abstract: To diagnose heparin-induced thrombocytopenia (HIT), detection of platelet-activating antibodies (HIT antibodies) is crucial. However, serum platelet activation profiles vary across patients and depend on test conditions. We evaluated the association between clinical outcomes and platelet-activating profiles assessed by a platelet microparticle assay (PMA), which detects activation of washed platelets induced by HIT antibodies, in 401 consecutive patients clinically suspected of having HIT. We made modification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Therefore, developing a sensitive approach to identify patients at high risk of HITT is critical for microsurgeries 25 . One of the clinical presentations of HITT is platelet consumption, which is directly related to the disease severity of HITT 54,55 . In this study, we found statistically significant differences in the percentage of platelet reduction on the first day postoperatively (21.0% in HITT and 14.0% in non‐HITT, p < 0.01).…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, developing a sensitive approach to identify patients at high risk of HITT is critical for microsurgeries 25 . One of the clinical presentations of HITT is platelet consumption, which is directly related to the disease severity of HITT 54,55 . In this study, we found statistically significant differences in the percentage of platelet reduction on the first day postoperatively (21.0% in HITT and 14.0% in non‐HITT, p < 0.01).…”
Section: Discussionmentioning
confidence: 52%
“…[16][17][18] We also measured platelet-activating antibodies by flow cytometric assay based on a platelet microvesicle assay (PMA), which detected the activation of washed platelets induced by activating heparin-dependent antibodies. 19 The PMA was performed as previously described by Maeda et al 19 by the evaluation of plateletactivating profiles, which detects the activation of washed platelets induced by activating antibodies in plasma or serum. In the SRA and PMA, platelet activation was challenged by an Fc-receptor-blocking monoclonal antibody (anti-CD32/FcγRIIA, clone IV.3; STEMCELL Technologies, Vancouver, BC, Canada) to confirm FcγRIIA engagement in platelets.…”
Section: Me Thodsmentioning
confidence: 99%
“…The platelet activation index (iPA) was calculated as previously described. 19 This iPA was obtained after sample analysis with flow cytometry to quantify the extent of washed-platelet activation. iPA is defined as the ratio (percentage) of the number of fluorescent events in the left upper quadrant to the total number of fluorescent events in the left and right upper quadrants combined.…”
Section: Me Thodsmentioning
confidence: 99%
“…(13) The washed platelet activation assay was performed as described in detail elsewhere. (2,14) In brief, washed platelets, prepared from HIT antibody-sensitive healthy volunteers, were used. Platelet microparticles, activated by HIT antibodies in a heat-inactivated serum, were quanti ed by ow cytometry.…”
Section: Data Collectionmentioning
confidence: 99%
“…(1) A segment of anti-PF4/heparin, an IgG with high titers, has platelet-activating properties which cause HIT. (2,3) In addition, these antibodies activate monocytes and endothelial cells leading to thrombocytopenia and a thrombin-induced hypercoagulable state. (4)(5)(6)(7) HIT is an atypical immune response when compared to other immune-mediated diseases caused by adaptive immunity (8-10): heparin-naïve patients can develop IgG antibodies as early as day 4, like a secondary adaptive immune response; evidence for an anamnestic response on heparin re-exposure is lacking; HIT antibodies are relatively short-lived unlike those from a secondary adaptive immune response.…”
Section: Introductionmentioning
confidence: 99%